Optimization of Early Childhood Motor Development (AUD) through Interactive Games at PAUD and Bethel Kindergarten Sentani - Tasijawa, Riski; Ugadje, Evelin F; Pattipeiluhu, Krislina; Wangguway, Yustinus; Kadio, Yarsenita; Rorimpandey, Enjeli; Suwarni, Maria T (Abdi Masyarakat, 2024)
Community service activities conducted by the Department of Early Childhood Christian Education (PKAUD) at STAKPN Sentani aim to enhance early childhood motor skills at PAUD and TK Bethel Sentani through interactive games. These activities include coconut shell stilts (egrang batok kelapa), role-playing with the theme of "buyers and sellers," and alphabet arranging with the theme of "arranging one's own name." The implementation of these games is expected to improve both gross and fine motor skills in children, as well as their cognitive and social abilities. Observations indicate that coconut shell stilts help with body balance and coordination, while role-playing and alphabet arranging enhance creativity, communication, and early literacy skills. This program not only provides practical benefits to PAUD and TK Bethel Sentani but also enriches academic insights in early childhood education literature.